Glide Insertion And Dialectal Variation In Kurdish - Hasan, Aveen Mohammed; Rasheed, Rebeen Abdulrahman (European Scientific Journal, ESJ, 2016)
One of the strategies used as a hiatus resolution is glide insertion. Previous Kurdish phonological works involve only a description of glide insertion in one dialect neglecting the segmental context. This study provides an analysis of glide insertion in word-medial vowel clusters in Kurdish and it is the first attempt to analyse the effects of dialect and segmental context. The speech material includes a set of words consisting of a stem plus a suffix with different vowel sequences at their boundaries. It is produced by four native speakers from four Kurdish speaking areas. The data analysis involves word transcription, their segmentation and the comparison of vowel sequences within and across the subdialects. The results indicate that glide insertion is not the only strategy used as word medial hiatus resolution, but it depends on the segmental context and dialect. Generally, the vowel hiatus is resolved by /j/ insertion. Vowel deletion is also used obligatorily in some segmental contexts when the second vowel in a sequence is /i/ and also when there are identical vowels in a sequences. Dialectal variations are observed in some vowel sequences in which /j/ insertion and vowel deletion both are used and when the first vowels in the sequence are the high back vowels in that /j/ and /w/ insertions are used. The findings suggests that /j/ insertion is the default strategy to resolve word-medial vowel clusters in Kurdish, the insertion of /w/ or vowel deletion are other strategies which are limited to some dialects and vowel sequences.